Meta-analysis for identifying the best method for chronic periodontitis therap - Bono, Alejandra (2018)
Fil: Bono, Alejandra, Liliana. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Periodoncia A; Argentina.